Inoculação de Azospirillum brasilense para amenização dos efeitos do déficit hídrico em plantas de milho, feijão, trigo e soja - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Water deficit is one of the major problems in agriculture worldwide, as it can cause severe damage to plant metabolism, resulting in significant losses that can exceed 50% depending on the crop development stage. Therefore, management practices aimed at mitigating water deficit represent one of the main challenges in the agricultural sector. Plants with longer root systems, characterized by greater length, smaller diameter, and higher incidence of longer root hairs, have greater potential for soil resource acquisition, biomass production, and assimilate formation. The use of plant growth-promoting bacteria has been a practice to enhance plant resistance to abiotic stresses, as they can improve root systems and produce phytohormones that mitigate the deleterious effects of water deficit. This study aimed to evaluate the effects of inoculating strains of Azospirillum brasilense, with and without water restriction, on the performance of maize, bean, wheat, and soybean under two water conditions. Experiments were conducted in a greenhouse at the State University of Ponta Grossa in the Centro-Sul region of Paraná, Brazil. The experiments followed a randomized complete block design in a 3 × 2 factorial scheme with three replications. Each experiment included the following treatments: without inoculation, inoculation with A. brasilense strains AbV5-AbV6, and inoculation with A. brasilense strain HM053; without and with water deficit. Water conditions were defined based on field capacity, where 80% represented the non-stress treatments and 40% represented the water deficit treatments. At 50 days after sowing, the following parameters were measured: net photosynthesis, stomatal conductance, intracellular carbon concentration, and transpiration in soybean and maize crops; chlorophyll readings, aboveground and root biomass production, and nutrient extraction by maize, beans, wheat, and soybean plants. The results were subjected to analysis of variance, and treatment effects involving inoculation with A. brasilense strains and water levels were compared using Tukey's test at the 5% significance level. Photosynthetic parameters in maize and soybean plants did not show significant responses to the use of AbV5- AbV6 or HM053 strains. For maize and wheat crops, chlorophyll a and b levels did not differ significantly for any of the variation sources, indicating that inoculation and water deficit did not influence these parameters in these crops. Maize plants inoculated with HM053 showed higher aboveground biomass and nitrogen extraction. Wheat plants exhibited improved root density when inoculated with HM053. In bean cultivation, co-inoculation with HM053 reduced chlorophyll a and b indices, as well as the number and mass of nodules and aboveground dry mass. The induction of water deficit significantly reduced chlorophyll b levels and bean biomass production. The use of A. brasilense strains AbV5-AbV6 and HM053 did not mitigate the negative effects of water deficit in the maize, soybean, wheat, and bean crops.
Keywords: Bactérias diazotróficas; déficit hídrico; nutrição de plantas; segurança alimentar; Diazotrophic bacteria; water deficit; plant nutrition; food security; CNPQ::CIENCIAS AGRARIAS:: AGRONOMIA